The function and regulation of myosin-interacting guanine nucleotide exchange factor (MYOGEF) and centrosome/spindle pole associated protein (CSPP) during mitotic progression and cytokinesis - Asiedu, Michael Kwabena (Kansas State University, 2007)
This dissertation describes the role of myosin-interacting guanine nucleotide exchange factor (MyoGEF) and centrosome/spindle pole associated protein (CSPP) in mitotic progression and cytokinesis. We have identified three mouse isoforms of CSPP, all of which interact and colocalize with MyoGEF to the central spindle in anaphase cells. The N-terminus of MyoGEF interacts with myosin whereas the C terminus interacts with the N-terminus of CSPP, forming a complex. The N-terminus of CSPP appears to be important for both localization and interaction with MyoGEF. CSPP plays a role in mitotic progression since its depletion by RNAi resulted in metaphase arrest. MyoGEF is required for completion of cytokinesis. Both MyoGEF and CSPP are phosphorylated by mitotic kinases including Plk1 and Aurora. Importantly, MyoGEF is phosphorylated at Thr-574 in mitosis by Polo-like kinase 1, and this phosphorylation is required for activation of RhoA. Thr-543 of MyoGEF is required for Plk1 binding in mitosis and phosphorylation of MyoGEF by Cdk1/cyclinB, possibly at Thr-543 may generate a Plk1 docking site, i.e., Cdk1 can phosphorylate MyoGEF at Thr-543, thereby allowing Plk1 to bind and phosphorylate MyoGEF at Thr-574. Finally, MyoGEF and CSPP are also phosphorylated by Aurora-B kinase in vitro. Taken together, we propose that Aurora-B may phosphorylate and recruit MyoGEF and CSPP to the central spindle, where phosphorylation of MyoGEF at Thr-543 promotes Polo kinase binding and additional phosphorylation of MyoGEF, leading to the activation of RhoA at the cleavage furrow.
Keywords: Guanine nucleotide exchange factor; MyoGEF; Centrosome proteins; Cytokinesis; Mitotic kinases; Mitotic progression; Biology, Cell (0379); Chemistry, Biochemistry (0487)